Dose-response relationship between 15 weeks of running and aerobic fitness: a retrospective analysis based on the fun running program - Zhixuan Tao; Xugui Sun; Jun Sun; Ergang Zhu (BMC, 2024)
Abstract Background Students' physical fitness, particularly aerobic fitness, has seriously declined during the COVID-19 epidemic. However, in the post-epidemic era, there are few studies on the methods of improving aerobic fitness. Understanding the dose-response relationship between physical activity and aerobic fitness is crucial for developing effective exercise prescriptions. Method This retrospective study reviewed the Fun Running program at Wannan Medical College in China. We conducted a pre-post study design to analyze the impact of 15 weeks of Fun Running training on aerobic fitness. Middle and long-distance running pace (MLDR-P) was used as the primary indicator of aerobic fitness. A paired sample T-test was used to analyze the differences between the two MLDR-Ps. Pearson's correlation was used to examine the correlation between variables. Multiple linear regression was used to determine the extent to which Fun Running components explain the variance in MLDR-P. Results A total of 3244 college students participated in this study. 15 weeks of Fun Running training can significantly improve the MLDR-P in both females (P < 0.001, ES = 0.68) and males (P < 0.001, ES = 0.72). The MLDR-P was significantly correlated with Fun Running (R2 = 0.95, p < 0.05, for females; R2 = 0.96, p < 0.05, for males). The component that had the greatest impact on MLDR-P was pace (β = 1.39, for females; β = 1.09, for males), followed by distance (β = 0.49, for females; β = 0.15, for males), and last frequency (β = -0.03, for all). Conclusion This study fills the gap in research on the dose-response relationship between running and aerobic fitness among college students in the post-epidemic era. The results show that 15 weeks of Fun Running training can significantly improve aerobic fitness. Examination of the dose-response relationship between Fun Running and MLDR-P provides practitioners with valuable insights into prescribing aerobic fitness training, allowing them to develop more effective training programs. Future research should focus on how to implement a hierarchical Fun Running program effectively.